A bibliometric analysis of undergraduate theses submitted to the Far Eastern University - Dr. Nicanor Reyes Medical Foundation from A.Y. 2009-2009 to 2014-2015 - Gonzales, Leanna Marie D.G.; Santos, Mark Anthony A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
The medical education and training today have increased in complexity, requiring more information than ever before. Therefore, libraries must frequently develop and evaluate their collection to continue to provide the users with the best services and most updated and reliable information that they need.
This study used citation and bibliometric analysis to examine the literature used in the Medical Technology, Physical Therapy and Nursing programs of Far Eastern University - Dr. Nicanor Reyes Medical Foundation from A.Y. 2008-2009 to 2014-2015 with a total of 2,836 citations gathered from 190 undergraduate theses. A citation index was generated containing the following elements: 1) title of the citing material; 2) title of the cited material; 3) author/editor of the citing material; 4) author/Editor i.e. [editor] of the cited material; 5) type of source material; 6) curricular program/field of study; 7) year of publication of the thesis title; 8) year of publication of the citation; 9) place of publication (local/foreign); and 10) other details such as journal title, book for articles and book chapter, link of electronic sources, name of websites cited as electronic sources, and newspaper or magazine titles for periodicals.
Results showed that Medical Technology had a total of 35 thesis titles, Physical Therapy with 12 titles and Nursing with 143 titles. The heavily cited type of source material was electronic sources consisting of 28.03% of the total citations. The results of the Medical Technology theses showed that the most cited source Wikipedia which was cited 15 out of 536 or 2.80% of the total cited sources. For Physical Therapy, the book Therapeutic Exercise: Foundations and Techniques by Kisner was the top cited source material with six citations or 4.48% of the total. For Nursing, the book Fundamentals of Nursing: Concepts, Process, and Practice was the most cited source with 25 citations or 1.17% of the total. The results also revealed the most cited author were A. Weissfeld, C. Kisner and B. Kozier for Medical Technology, Physical Therapy and Nursing respectively. The time distribution in the Medical Technology program showed that 390 out of 536 citations or 72.76% of the total cited materials were publications from the year 1996 up to 2015. In the Physical Therapy program, the results displayed that 93 or 69.40% of the citations were published from 2006 to 2014. In the Nursing program, 986 or 45.52% of the citations were published in 1992 to 2005. From the years 2006 to 2015, citations were published 754 times gathering only 34.81% of the total citations.
It is recommended that the FEU-NRMF provide access to more electronic journals and acquire more updated reference books. Also, it is suggested to promote and recommend other type of source materials, particularly printed materials such as newspapers and magazines for students to consider the use of such type of references. For the storage and retention policies of the library, the library should keep the sources with 15 years of age or the most recent source materials. Lastly, it is highly recommended that the institution add more reliable sources in their collection such a medical dictionaries and encyclopedias to lessen the students'dependence in online dictionaries.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Far Eastern University - Dr. Nicanor Reyes Medical Foundation; Bibliometrics; Citation of electronic information resources; Citation indexes; Dissertations, Academic -- Philippines -- Quezon City